PENGETAHUAN MAHASISWA DAN TENAGA KEPENDIDIKAN TENTANG IMPLEMENTASI MBKM DI PROGRAM STUDI PENDIDIKAN PROFESI BIDAN UNIVERSITAS MEGA BUANA PALOPO - Yuniar Dwi Yanti Yuniar Dwi Yanti; Ishak Ishak; Evawati Uly Evawati Uly (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
Background: Independent Campus is one of the policies of the Minister of Education and Culture who gave a university policy to give the right to study for three semesters outside the study program. The Independent Learning Policy of the Kampus Merdeka is to encourage students to master various fields of knowledge according to their fields of expertise so that they are ready to compete in the global world. Objective: This study aims to measure the knowledge of students and education staff in implementing the Merdeka Belajar program at Kampus Merdeka within the scope of the Midwifery Professional Education Study Program, Faculty of Health, Mega Buana Palopo University. Method: This research is quantitative research with an analytical survey method. The sample is midwifery students and educational staff with total sampling technique of 210 people. Data analysis using computer program. Result: Respondents' knowledge about the implementation of MBKM is in the fairly good category with the number of respondents who answered quite well is 107 people (50.9 percents). Conclusion: Respondents' knowledge about the implementation of MBKM is in the fairly good category